DAMPAK PENGGUNAAN JEJARING SOSIAL (FACEBOOK) TERHADAP KOMUNIKASI VERBAL PELAJAR DI SMK DDI PAREPARE - Nur Aulia Angraeni; Uswatun hasanah; Nurhakki nurhakki (KOMUNIDA : Media Komunikasi dan Dakwah, 2016)
This study aimed to find out how big the response of students to the social networks and examines the impact of the use of social networking on verbal communication and non-verbal students in vocational DDI Pare Pare. This study used descriptive qualitative approach that describes the impact of social networking through analysis and using observation, interview and documentation as well as based on the learner activity. This study is based on the theory of Raph Larosa and C. Reitzes (1993) they assume that the individual development can occur through interaction with others. In line with the George Herbert Mead (1934) argued that humans should develop ideas through interaction with others. Burhan (2009) adds that technology has created a global interaction so that each individual has unwittingly created a real society and virtual communities. These results indicate that the positive and negative impact on the use of social networking verbal and nonverbal personal communication students in vocational DDI Pare Pare is reflected in the way we communicate and gestures they use. The written language they use to interact consciously or not often they say. While their non-verbal language reflected yan code they use in life nayata.